Design and characterization of polycaprolactone-gelatin-graphene oxide scaffolds for drug influence on glioblastoma cells. (June 2019) - Unal, Semra; Arslan, Sema; Gokce, Tilbe; Atasoy, Beste Melek; Karademir, Betul; Oktar, Faik Nuzhet; Gunduz, Oguzhan
Graphical abstract: 3D PCL-Gel-GO composite scaffolds in the form of layer-by-layer structure were successfully fabricated by combining electrospinning and electrospraying techniques. The scaffolds were fabricated to mimic extracellular matrix of glioblastoma. Drug combination with radiation therapy were compared in 2D and the 3D scaffolds. Highlights: PCL-Gelatin (Gel)-Graphene oxide (GO) scaffolds were produced by the combination technique of electrospinning and electrospraying using various GO ratio. PCL-Gel-GO scaffolds provide a 3D microenvironment for glioblastoma cells that mimic of the in vivo tumor. Gel and GO particles can be well dispersed on the PCL scaffold as a form of sandwich structure by using the combination technique. Abstract: Three-dimensional (3D) scaffolds that mimic in vivo tumor microenvironments can be used to study tumor response to anticancer treatments, since most preclinical combination treatment strategy for anti-glioma were evaluated with traditional 2D cell culture. In this research, the nanofiber scaffolds of polycaprolactone (PCL) containing gelatin (Gel) nano/microparticles coated with different concentrations of graphene oxide (GO) and were successfully produced by combining electrospinning and electrospraying techniques. Scanning electron microscope (SEM), Fourier-transform infrared (FT-IR) spectroscopy and mechanical testing were used to characterize the structure and properties of the composites. The results show that gelatin and graphene particles can be well dispersed in the polycaprolactone nanofiber matrix by using the combination technique of electrospinning and electrospraying. The presence of 1 wt% graphene oxide increased mechanical strength of PCL/Gel scaffold and was found to be well consistent with the drug treatments (temozolomide and bortezomib) and radiotherapy by not showing additional toxicity.